Peri-Implant Diseases: Diagnosis, Clinical, Histological, Microbiological Characteristics and Treatment Strategies. A Narrative Review - Ioannis Kormas; Chantal Pedercini; Alessandro Pedercini; Michail Raptopoulos; Hatem Alassy; Larry F. Wolff (MDPI AG, 2020)
Since the use of dental implants is continuously increasing, it is imperative for dental practitioners to understand the nature and treatment of peri-implant diseases. The purpose of this manuscript is to comprehensively review peri-implant diseases, their characteristics, as well as their non-surgical and surgical treatment. To that end, the current literature was searched and a narrative review was conducted. It is essential that the case definitions described in the 2017 World Workshop on the Classification of Periodontal and Peri-implant Diseases and Conditions are used to diagnose and classify peri-implant health, peri-implant mucositis and peri-implantitis. While recent epidemiologic studies on peri-implant diseases exist, there is great heterogeneity in the definition of these conditions. Several risk factors and indicators are reported in the literature, with smoking and diabetes being the most universally accepted. In peri-implant mucositis, non-surgical treatment seems to be sufficient. However, for the treatment of peri-implantitis, a surgical approach, which includes open-flap debridement, apically positioned flap and guided bone regeneration, is considered more appropriate. A great variety of adjuncts to mechanical treatment have been reported with controversial results. Finally, studies comparing results from different peri-implantitis treatments are warranted in randomized controlled clinical trials in order to provide stronger evidence-based approaches.